2019
DOI: 10.1186/s12885-019-6160-9
|View full text |Cite
|
Sign up to set email alerts
|

Geographic distribution and risk of upper urothelial carcinomas in Croatia, 2001–2011

Abstract: Background Strong associations exist between Balkan endemic nephropathy (BEN) and upper urothelial carcinomas (UUCs). However, the common etiology between the two remains unclear and there are no studies to date that visualize UUC risks in Croatia. In Croatia, 14 villages in the southwestern part of Brod-Posavina County are considered endemic for BEN. The aim of this ecological study is to map cancer risks and describe the case distribution of UUCs in Croatia at the county level during 2001–201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…Five studies reported on incidence of UTUC according to specific geographical regions [ 14 , 24 , 31 , 34 , 37 ]. The study by Mathew et al [ 37 ] covered 10 regions for both males and females, and a further five regions for males.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies reported on incidence of UTUC according to specific geographical regions [ 14 , 24 , 31 , 34 , 37 ]. The study by Mathew et al [ 37 ] covered 10 regions for both males and females, and a further five regions for males.…”
Section: Resultsmentioning
confidence: 99%
“…Visser et al [ 14 ] further reported incidence in different regions of Europe between 1995 and 2002 and found northern Europe to have the highest ASR of 12.8 (SE 0.3) per million persons. The high incidence of UTUC in regions with a high prevalence of Balkan endemic nephropathy (BEN) was studied by Medunjanin and colleagues [ 31 ], who reported a high incidence in Croatia geographically associated with a high prevalence of BEN, specifically in the Brod-Posavina county.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that, if the tumourigenic agent had generally been in vascular circulation, and then in kidney glomerular filtrate, it only targeted pelvis epithelium without affecting epithelia of the various nephron segments. A recent study of urothelial carcinomas across Croatia [18] cites historic incidence of upper urothelial tract tumours of the ureter and renal pelvis as 5-10 % of all cases, with notably higher incidence in the Slavonski Brod area where the Balkan nephropathy has been endemic for many years. Half of the upper urothelial cancers (n = 608) were in the renal pelvis, both nationally and specifically in the urban area of Zagreb (n = 107) and the rural area around Slavonski Brod (n = 86).…”
Section: Discussionmentioning
confidence: 99%
“…Specifičnost EN-a je značajno povećan rizik za razvoj UTUC-a 7,11 . Istraživanja u Republici Hrvatskoj pokazala su kako je i do 55 puta veći specifični mortalitet od navedenog karcinoma u endemskim područjima nego u ostalim dijelovima Hrvatske 12,13 . Zbog toga sve pacijente s EN-om treba redovito kontrolirati kako bi se UTUC otkrio u što Karcinomi prijelaznog epitela gornjeg dijela mokraćnog sustava izrazito su rijetki zloćudni tumori.…”
Section: Slikaunclassified